Evaluation Of Madrasah Extracurricular Programs During The Covid 19 Pandemic - Zawaqi Afdal Jamil; Muhammad Munawir Pohan; Mahmud Hibatul Wafi (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2021)
This study aims to evaluate the PTP-VI Private Madrasah Aliyah Berangir extracurricular program, North Labuhanbatu Regency, North Sumatra, during the covid 19 pandemic. The scope of the evaluation used in program evaluation includes four levels, namely evaluation of context, input, process, and product. This program evaluation research uses a qualitative method with a case study approach. Data were collected by observation, interviews, and document studies. Data analysis techniques are data presentation, data reduction, data verification, and concluding. Test the validity of the data through credibility, dependability, and confirmability tests. The data sources in this study were the head of the madrasa, the deputy head of the madrasa in the field of curriculum, and all extracurricular coaches. From the study results, it was found that the context level was relatively good. The entire program of extracurricular activities evidences this following the madrasa's vision, mission, goals, and needs of the madrasa and students. At the level of relatively good input, all extracurricular teachers have met the qualifications in their respective fields. Previously, the coaches achieved at the sub-district, district, and provincial levels. The process level is relatively good because the planning is done carefully in curriculum, teacher coaches, facilities, and schedules. The product level is not good because only specific extracurricular fields have proud achievements, but other extracurricular areas or branches are not followed.